(untitled) (Research, Society and Development, 2021)
Brazil has an abundant agricultural productivity and as a result, there is an increasing use of agricultural pesticides. However, many times, there is not an adequate disposal of the empty packaging of this pesticide, thus causing direct negative interference in the environment. As a result of these facts, reverse logistics was implemented in order to solve the problem of environmental degradation caused by the improper disposal of said packaging. Despite all legislative mechanisms, it appears that reverse logistics does not work in its entirety. Thus, in the present work, some analyzes are made about the main problems for the effective implementation of reverse logistics of empty pesticide packaging. To do so, it starts from a bibliographic research that seeks to assemble the theoretical substrate used in the analysis of the problem from the analysis and some empirical research carried out in some regions of Brazil and the analysis of the relevant legislation. It was possible to verify that the main obstacles to reverse logistics are the omission of the law, bureaucratization, lack of structure for both rural producers and other agents in the agribusiness chain and, finally, the lack of strict inspection by the government. public. The solution shown by the authors of the empirical research was to reanalyze the legislation, as well as the structures imposed on environmental awareness based on an education relevant to this point, which is fundamental to facilitate the effective implementation of reverse logistics of empty pesticide packaging in Brazil.